Inaugural Lecture - Kabale University (Kabale University, 2023)
Prof. Sabiti Makara is a Professor in the Department of Governance at Kabale University in Uganda. Before joining Kabale University in 2023, he had served as a Professor at Makerere’s Department of Political Science & Public Administration for long. Prof. Makara has done extensive research on governance issues: public sector reforms, constitutional-ism, election management, political parties, civil society, urban governance and local governance. In the course of his long academic career, he won research grants from SIDA, the Ford Foundation, UN Women (Uganda), Norwegian Research Council, UNDP, African Union Commission, Electoral Institute for Southern Africa (EISA), French Institute for Research in Africa (IFRA), International Institute for Democracy and Electoral Assistance (IDEA), UNESCO Regional Office, Nairobi, Irish Aid/University of Limerick (Republic of Ireland), Chr. Michelsen Institute (CMI) Norway, and the Democratic Governance Facility (DGF). He took research residence at University of Antwerp (Belgium), CMI Bergen, University of Bergen, Norway, Steamboat Springs, Colorado US, and Chinese Academy of Social Sciences (CASS) in Beijing. He served a Senior Consultant for EU -funded projects in Uganda, did an assessment for USAID’s Multiparty Support Project in Uganda, Mid-term assessment of DGF’s support for Civil Society, Team Leader for UNDP’s support to the Parliament of Uganda (establishment of its own TV and Radio); and is regularly consulted by the Ministry of Local Government and other Ministries and MDAs. Prof. Makara graduated with a PhD in Political Studies at Wits University (South Africa), MPA from the University of Liverpool (UK) and a BA (Hons.) majoring in Political Science from Makerere University. Prof. Makara is widely published in internationally recognized journals, and book chapters. He has edited 4 books and co-authored one. He loves teaching, and has supervised over 100 graduate students to completion. He serves as External Examiner for 8 universities.